UPAYA PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL DISCOVERY LEARNING MATERI MATEMATIKA TEMA 7 KELAS III SDN PESAREN 02 TAHUN PELAJARAN 2020/2021 - Nailul Fauzziyah; Mei Fita Asri Untari; Ulin Nafiah (JS (JURNAL SEKOLAH), 2021)
Abstract : Efforts to Improve Student Learning Outcomes Through the Discovery Learning Model for Math Material Theme 7 Class III SDN Pesaren 02 Academic Year 2020/2021. PTK. Teacher Professional Education Study Program, Postgraduate Faculty, PGRI University Semarang. Supervising Lecturer Mei Fita Asri Untari, S.Pd., M.Pd., Tutor Ulin Nafiah, S.Pd. The background that drives this research is the learning outcomes of third grade students at SD Negeri Pesaren 02 in the Mid-Semester Assessment (PTS) who achieve the Minimum Completeness Criteria (KKM) only get an average score of 60. This is due to students who are less focused when learning and also as a result of the Covid-19 Pandemic full online learning, causing students to become less understanding and less aware of the material conveyed by the teacher. The problem in this research is how to improve learning outcomes through the Discovery Learning learning model in class III Theme 7 at SD Negeri Pesaren 02 for the 2020/2021 academic year. This study aims to improve learning outcomes, especially in the content of mathematics lessons. This type of research is Classroom Action Research (CAR). The subjects of this study were all third grade students at SD Negeri Pesaren 02, totaling 26 consisting of 16 male students and 10 female students. The object under study is student learning outcomes in the content of mathematics lessons. The results of this study are in the first cycle the average value of learning outcomes is 73.50 with an average percentage of learning completeness of 32.5%. In the second cycle the average value of learning outcomes is 63.50 with an average percentage of learning completeness of 64%. In cycle III the average value of learning outcomes is 89.50 with an average percentage of learning completeness of 88.5%. That from the first cycle to the second cycle, the average score increased by 10 with a percentage increase of 31.5% in mastery learning outcomes. Then the increase in the average value from cycle II to cycle III is 16 with a percentage increase in learning outcomes of 24.5%. Thus, it can be seen that in the third cycle, the indicators of success have been achieved with the achievement of mastery learning outcomes that is equal to 88.5%. So it can be concluded that the Discovery Learning model can improve the learning outcomes of class III Theme 7 students at SD Negeri Pesaren 02 for the 2020/2021 academic year.Keywords: CAR, discovery learning, learning outcomesAbstrak : Upaya Peningkatan Hasil Belajar Siswa Melalui Model Discovery Learning Materi Matematika Tema 7 Kelas III SDN Pesaren 02 Tahun Pelajaran 2020/2021. PTK. Program Studi Pendidikan Profesi Guru Fakultas Pasca Sarjana Universitas PGRI Semarang. Dosen Pembimbing Mei Fita Asri Untari, S.Pd., M.Pd., Guru Pamong Ulin Nafiah, S.Pd. Latar belakang yang mendorong penelitian ini adalah hasil belajar peserta didik kelas III di SD Negeri Pesaren 02 pada Penilaian Tengah Semester (PTS) yang mencapai Kriteria Ketuntasan Minumal (KKM) hanya mendapat nilai rata-rata 60. Hal ini disebabkan peserta didik yang kurang fokus saat pembelajaran dan juga akibat dari Pandemi Covid-19 pembelajaran full daring, Sehingga menyebabkan siswa menjadi kurang memahami dan kurang mengetahui materi yang di sampaikan dari guru. Permasalahan pada penelitian ini adalah bagaimana meningkatkan hasil belaajr melalui model pembelajaran Discovery Learning pada kelas III Tema 7 di SD Negeri Pesaren 02 Tahun Pelajaran 2020/2021. Penelitian ini bertujuan untuk meningkatkan hasil belajar khususnya pada muatan pelajaran matematika. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK). Subjek penelitian ini adalah seluruh siswa kelas III di SD Negeri Pesaren 02 yang berjumlah 26 yang terdiri dari 16 siswa laki-laki dan 10 siswa perempuan. Adapun objek yang diteliti adalah hasil belajar siswa dalam muatan pelajaran matematika. Hasil penelitian ini adalah pada siklus I rata-rata nilai hasil belajar yaitu 73,50 dengan rata-rata persentase ketuntasan belajar sebesar 32,5%. Pada siklus II rata-rata nilai hasil belajar yaitu 63,50 dengan rata-rata persentase ketuntasan belajar sebesar 64%. Pada siklus III rata-rata nilai hasil belajar yaitu 89,50 dengan rata-rata persentase ketuntasan belajar sebesar 88,5%. Bahwa dari siklus I ke siklus II mengalami peningkatan nilai rata-rata sebesar 10 dengan persentase peningkatan ketuntasan hasil belajar sebesar 31,5%. Kemudian peningkatan nilai rata-rata dari siklus II ke siklus III sebesar 16 dengan persentase peningkatan ketuntasan hasil belajar sebesar 24,5%. Dengan demikian dapat diketahui bahwa pada siklus III sudah mencapai indikator keberhasilan dengan pencapaian ketuntasan hasil belajar yaitu sebesar 88,5%. Sehingga dapat disimpulkan bahwa model Discovery Learning dapat meningkatkan hasil belajar siswa kelas III Tema 7 di SD Negeri Pesaren 02 Tahun Pelajaran 2020/2021.Kata Kunci: PTK, discovery learning, hasil belajar